2021
DOI: 10.1177/1542316620986138
|View full text |Cite
|
Sign up to set email alerts
|

Jirga System and Its Role in Peacebuilding and Development in Pakistan’s Terrorism-Affected Pashtun “Tribal” Districts

Abstract: Pakistan’s erstwhile Federally Administered Tribal Areas (FATA) have suffered a lot due to terrorism and extremism after the 9/11 attacks in the United States because these areas were used by local and transnational militant groups as a haven after the U.S. invasion of Afghanistan in 2001. These groups attacked the security forces, the local tribal leaders, and all those who opposed them and killed, many of them to get control over these areas. This resulted in huge physical, economic, social, and psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In contrast, it helps to remove division and it helps to bring a feeling of togetherness and tolerance. In line with this, the Jorga system in Pakistan played a significant role in peace-building and restoration in Pashtun tribal districts (Alam, 2021). Another study which was conducted in the Somali region of Ethiopia indicated that the majority of the respondents preferred to settle conflicts through indigenous mechanisms (Bouh and Mammo, 2008).…”
Section: Resultsmentioning
confidence: 86%
“…In contrast, it helps to remove division and it helps to bring a feeling of togetherness and tolerance. In line with this, the Jorga system in Pakistan played a significant role in peace-building and restoration in Pashtun tribal districts (Alam, 2021). Another study which was conducted in the Somali region of Ethiopia indicated that the majority of the respondents preferred to settle conflicts through indigenous mechanisms (Bouh and Mammo, 2008).…”
Section: Resultsmentioning
confidence: 86%
“…and finally, the fee of the advocate. However, the DRC mechanism is totally free of cost and quick justice delivery system, only the transportation cost, were borne by the disputants, while no charges were filed against the mediator/advocate and the case (Alam, 2021). The study area, rural in nature, various kinds of cases/disputes were found between family/relative, friend/business partner, neighbor, community members, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A research study carried out in Afghanistan points out that the judicial system involved in various illegal ways i.e. long delays in cases and corruption to resolve a conflicting situation resulted in people preferring to resolve their issues through mutual cooperation through Jirga or dispute resolution council/local council (Wardak, 2002; and Alam, 2021). One of the studies carried out in America and other regions concluded that due to the excessive cost and delay in the litigation system the people were inclined towards the ADR for resolution of their disputes, as the ADR was one of the alternates of the formal courts and also more efficient ways of providing access to justice (Burger, 1976; Woolf, 1996; and Khan et al ; 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations